Visual Design of Artificial Intelligence Based on the Image Search Algorithm - Jiang, Xiaobo; Chen, Zongren; Yu, Jun; Huang, Lixia (Journal of Applied Data Sciences, 2020)
With the rise of the wave of artificial intelligence and the development and popularization of intelligent technology, the digital images generated by the Internet and mobile intelligence terminals grow exponentially. As the most important information carrier of data content, pictures occupy immeasurable value in this era. To solve the shortage of image search engines, this paper uses the image browsing algorithm, which combines the semantic and image characteristics of the image, and organizes the returned images according to the visual characteristics similarity of the images. In addition, in order to reduce the computational time and improve the performance of similarity search, a near neighbor search algorithm based on key dimensions is applied. Experiments show that the AI visualization design based on the image search algorithm can not only overcome the semantic gap to some extent, but also strengthen the interaction between 88% systems and users to browse the search results more efficiently and naturally.